Reconciling Civil Recovery and Prosecution in the Fight Against Grand Corruption - Mustafa, Cecep; Komalasari, Rita (The Prosecutor Law Review, 2024)
This essay seeks to explore the treatment of grand corruption and the legal categorization of civil recovery regimes. It aims to provide fresh insights into the interface between combating corruption and protecting human rights. Specifically, it questions whether grand corruption should be primarily treated as a criminal offense and examines the human rights concerns raised by the civil recovery approach. Moreover, it introduces clear criteria for balancing these competing imperatives. The research employs a literature approach, drawing from legal, human rights, and anti-corruption literature. This essay presents a twofold conclusion. First, it argues that grand corruption should be predominantly treated as a criminal offense, challenging the prevailing emphasis on civil recovery. This research offers fresh insights into reconciling these conflicting imperatives and informs future policy and legal developments in the fight against corruption.